2021
DOI: 10.1055/s-0041-1733904
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Neutrophil-to-Lymphocyte Ratio, Red Blood Cell Distribution Width, and Mean Platelet Volume in Predicting Febrile Seizures and Differentiating Febrile Seizure Types

Abstract: The neutrophil-to-lymphocyte ratio (NLR), red blood cell distribution width (RDW), platelet count (PLT), and mean platelet volume (MPV)/platelet ratio (MPR) are commonly known inflammatory markers measured by a routine peripheral blood test that have been studied in patients with febrile seizures (FS) and may be useful for the classification of FS types. The aim of this study was to investigate the relationship between FS and inflammatory markers including MPR, RDW, and NLR and also to determine the diagnostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…46 In another study, NLR was reported to be beneficial to differentiate not only febrile seizure from fever without seizure but also simple febrile seizure from complex febrile seizure. 45 NLR was also stated in other studies as a distinctive parameter for complex and simple febrile seizures. 10 11 However, studies in which NLR was not statistically different between the patient and control groups also make the issue even more controversial.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…46 In another study, NLR was reported to be beneficial to differentiate not only febrile seizure from fever without seizure but also simple febrile seizure from complex febrile seizure. 45 NLR was also stated in other studies as a distinctive parameter for complex and simple febrile seizures. 10 11 However, studies in which NLR was not statistically different between the patient and control groups also make the issue even more controversial.…”
Section: Discussionsupporting
confidence: 54%
“…Indeed, low MPV levels were reported to be in favor of complex febrile seizures in the differentiation of febrile seizure types. 45 A study by Güneş and Büyükgöl 8 found no significant difference in the MPV values between patients with generalized seizures and healthy controls. This study did not detect any evidence of significant difference in remission durations of SeLECTS patients based on the MPV levels.…”
Section: Discussionmentioning
confidence: 96%
“…The association between FS and inflammatory factors has been increasingly studied. NLR has been recognized as a risk factor for FS in multiple studies, including meta-analyses, and is now regarded as a cost-effective diagnostic biomarker for the disease [ 16 , 17 , 32 – 34 ]. Several studies have also reported an association between NLR and FS recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also reported an association between NLR and FS recurrence. Bril et al found that an elevated NLR posed a significant risk for FS recurrence (OR = 2.64, 95% CI: 1.17–4.85) [ 17 ]. In our study, Neutrophil count was significantly different between two groups ( P = 0.007)with lower level observed in the recurrent group compare to the non-recurrent group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation